1990
DOI: 10.1111/j.1365-2125.1990.tb03657.x
|View full text |Cite
|
Sign up to set email alerts
|

The comparative effects of paracetamol and indomethacin on renal function in healthy female volunteers.

Abstract: 1 Renal function was assessed in 10 healthy female volunteers during administration of placebo, paracetamol (acetaminophen) (4.0 g daily) and indomethacin (150 mg daily) for 3 days under conditions of controlled sodium and fluid intake. 2 Paracetamol and indomethacin had no significant effect on the glomerular filtration rate and effective renal plasma flow as measured by the renal clearances of inulin, creatinine and p-aminohippurate (PAH). 3 Compared with placebo, paracetamol reduced the mean urinary excreti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…However, IMC is a potent prostaglandin synthesis inhibitor, and the mechanisms other than transporter inhibition have been implicated in its inhibitory effects. In addition, although there are reports that IMC had no effect on creatinine renal clearance in humans (Levey et al, 1988;Prescott et al, 1990), the unchanged clearance could be confounded by consumption of a high-protein meal (Levey et al, 1988). Information about the inhibition of creatinine clearance by BSP in humans is lacking, because BSP is a contrast agent used as a diagnostic aid in liver function test.…”
Section: Discussionmentioning
confidence: 99%
“…However, IMC is a potent prostaglandin synthesis inhibitor, and the mechanisms other than transporter inhibition have been implicated in its inhibitory effects. In addition, although there are reports that IMC had no effect on creatinine renal clearance in humans (Levey et al, 1988;Prescott et al, 1990), the unchanged clearance could be confounded by consumption of a high-protein meal (Levey et al, 1988). Information about the inhibition of creatinine clearance by BSP in humans is lacking, because BSP is a contrast agent used as a diagnostic aid in liver function test.…”
Section: Discussionmentioning
confidence: 99%
“…Acetaminophen at daily doses of Ͼ500 mg has been shown to inhibit prostacyclin synthesis in humans, which may diminish gastric mucosal protection (13), and to affect kidneys, neural tissue, and platelets (37)(38)(39)(40)(41). Results of a recent study by Catella-Lawson et al showed that acetaminophen at high doses is a weak, reversible, isoform-nonspecific COX inhibitor and suggested that 3052 RAHME ET AL acetaminophen may have GI side effects (16).…”
Section: Discussionmentioning
confidence: 99%
“…Indomethacin is a relatively potent in vitro inhibitor of OAT2 (IC 50 = 2.1 mM) (Shen et al, 2015). However, the effect of indomethacin on elevation of SCr in several clinical studies is controversial (Prescott et al, 1990;Al-Waili, 2002). In female healthy volunteers, indomethacin (150 mg daily for 3 days) had no significant effect on SCr, GFR, or renal blood flow (Prescott et al, 1990).…”
Section: Inhibition Of Renal Transporters and Elevation Of Scr: An Inmentioning
confidence: 99%
“…However, the effect of indomethacin on elevation of SCr in several clinical studies is controversial (Prescott et al, 1990;Al-Waili, 2002). In female healthy volunteers, indomethacin (150 mg daily for 3 days) had no significant effect on SCr, GFR, or renal blood flow (Prescott et al, 1990). However, indomethacin was reported to increase SCr in neonates (AlWaili, 2002).…”
Section: Inhibition Of Renal Transporters and Elevation Of Scr: An Inmentioning
confidence: 99%